Gain or loss? Examining the dual effects of small talk on employees’ safety performance - Liu, Pan; Zhang, Mingyu; Guo, Ru; Duan, Caili; Shi, Bixiang; Wei, Bolu (Frontiers in Psychology, 2025)
IntroductionSmall talk, an informal social interaction in workplaces, has been overlooked in research on safety performance, which traditionally focuses on organizational factors (e.g., safety climate, leadership). Grounded in Conservation of Resources (COR) theory, this study explores its dual effects on employees’ safety performance, proposing that small talk may enhance safety performance via resource gain (psychological availability) and undermine it via resource loss (work absorption).MethodsData was collected from 136 full-time employees in China through self-reported questionnaires, measuring small talk, psychological availability, work absorption, and safety performance. Path analysis and bootstrapping approach were conducted to test for the direct and indirect effects of small talk.ResultsThe results confirmed the dual effects of small talk on safety performance: small talk positively predicted safety performance through increasing psychological availability, while negatively predicted safety performance by reducing work absorption.DiscussionThis study advances safety research by highlighting small talk as a micro-level determinant of safety performance, and enriches COR theory by illustrating resource gain/loss mechanisms in social interactions. Practically, it offers insights for managing informal communication to balance relational benefits and task focus, optimizing workplace safety.